2020
DOI: 10.2147/hiv.s265101
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of HIV/AIDS Among Elderly People and Associated Factors in Habru Woreda, Amhara Region, Northeast Ethiopia</p>

Abstract: Introduction: Sub-Saharan African countries are the most affected region by HIV/AIDS. Data from Demographic and Health Survey (DHS) indicated that in Ethiopia older adults who are HIV positive were 2.1% which accounted 17.7% from all HIV positive people aged ≥15. Scarce data are available regarding the prevalence of HIV and associated factors among elderly peoples in Habru district. Objective: To assess the prevalence of HIV and associated factors among older people ≥50 years' age in the study area. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A previous similar study conducted in Ethiopia (23) showed that adults are at high risk for contracting HIV/ADIS. In contrast, a study conducted in the Habru district in the Amhara region, Ethiopia (21), indicated that older people are more likely to be infected.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A previous similar study conducted in Ethiopia (23) showed that adults are at high risk for contracting HIV/ADIS. In contrast, a study conducted in the Habru district in the Amhara region, Ethiopia (21), indicated that older people are more likely to be infected.…”
Section: Discussionmentioning
confidence: 87%
“…Several prior studies have been conducted in other places and Ethiopia to investigate HIV by age (21), sex disparities (22)(23)(24)(25), VL surveillance evaluation(26-29), VL suppression coverage status (7,10,(30)(31)(32)(33)(34)(35), factors that contribute to no VS (23,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), HIV VL program bene ts (22,32,(46)(47)(48)(49)(50), the prevalence of HIV, treatment gaps, and geographical location (9,13,(51)(52)(53). However, few of these studies have focused on evaluating the ability of laboratory-based surveillance systems to predict HIV viral load suppression by 2030.…”
Section: Introductionmentioning
confidence: 99%
“…This highlights yet another high-risk group infected with human immunodeficiency virus (HIV). 1,2 In 2017, for the first time in China, the older adults, together with migrant workers who may be sexually active, young students, overseas labor workers, and monitored drug users in treatment programs, were included in the key groups surrounding AIDS prevention and control. 3 Depending on the route of AIDS transmission, elderly AIDS patients often feel internal shame for violating traditional moral values.…”
mentioning
confidence: 99%
“…The number of reported AIDS cases among people 50 years and older has been increasing annually, with the aging of the global population. This highlights yet another high-risk group infected with human immunodeficiency virus (HIV) 1,2 . In 2017, for the first time in China, the older adults, together with migrant workers who may be sexually active, young students, overseas labor workers, and monitored drug users in treatment programs, were included in the key groups surrounding AIDS prevention and control 3 .…”
mentioning
confidence: 99%